Answer:
Hence experimental probability that all 3 coins show the same result when he tossed it for 50 times and 8 of those are of success is 0.04
Step-by-step explanation:
Given:
3 coins are tossed at same time
No of trails are 50 and
success for trails are 8.
To Find:
Experimental probability for 3 coins that getting all heads or all tails.
Solution:
Now
When only 3 coins are tossed probability that getting all heads is as follows:
Calculating the sample space of the event
Event is 3 coins are tossed at a time
So Sample space S={HHH,HHT,HTH,HTT,THH,THT,TTH,TTT}
n(S)=8
No of trails getting all heads is 1
So P(getting all heads )=1/8
Same of tail i.e. 1/8
Adding both will be required probability for getting all heads or tails
here or ' operator so Addition
1/8+1/8=2/8
=1/4
1/4 is probability that the all heads or all tails when coins is tossed one time
but here it is about 50 times and probability if successs trails are 8
Hence
Now
Probability of success P=8/50=0.16
Probability of getting all heads and all tails in 50 trails of which 8 are only success
Hence required Probability =Probability of success *Probability of getting all heads or tails
=0.16*(1/4)
=0.16*0.25
=0.04
Hence experimental probability that all 3 coins show the same result when he tossed it for 50 times and 8 of those are of success is 0.04
2.) 3.75
I need the answer to these two, for the 0.83 I got 83/100
The solution of the equation is -2x - 7y = -4
What is an Equation?
Equations are mathematical statements with two algebraic expressions flanking the equals (=) sign on either side.
It demonstrates the equality of the relationship between the expressions printed on the left and right sides.
Coefficients, variables, operators, constants, terms, expressions, and the equal to sign are some of the components of an equation. The "=" sign and terms on both sides must always be present when writing an equation.
Given data ,
Let the value of addition of both equations be = C
Let the first equation be represented as = A
The value of A is
5x - 9y = 1 be equation (1)
Let the second equation be represented as = B
The value of B is
-7x + 2y = -5 be equation (2)
Now , the addition of equation (1) + equation (2) is
The value of C is = equation (1) + equation (2)
The value of C is 5x - 9y = 1 + -7x + 2y = -5
5x + ( -7x ) = -2x
-9y + 2y = -7y
1 + ( -5 ) = -4
Therefore , the equation is -2x - 7y = -4
Hence , the solution of equation C is -2x - 7y = -4
To learn more about equations click :
#SPJ2
Answer:
Solution = -2x-7y=-4
Step-by-step explanation:
Add the x-component to the x-component, add the y-component to the y-component, add the number to the number.
It looks like this
5x + (-7x) = -2x
9y + (-2y) = -7y
1 + (-5) = -4
Then, put the solutions in the places where you see them in the equation, x goes first, y comes second, then this equals the number value.
-2x - 7y = -4
Answer:
Snakes to lizards: 6:2
Lizards to all reptiles: 2:8
Step-by-step explanation:
I am sorry if I am wrong. And if I am right yay! Though I am pretty sure I am right-
Answer:
3/5
2/5
Step-by-step explanation: